2006
DOI: 10.1111/j.1365-2893.2006.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characteristics of hepatitis B virus genotype C subgenotypes in China*

Abstract: Genetic diversity within the same hepatitis B virus (HBV) genotype indicates the presence of several subgenotypes. We have found that genotype C is the most common in China, and this study aimed to determine the geographical distribution and characteristics of HBV-C subgenotypes in the country. A cohort of 534 patients with chronic HBV genotype C infection, collected across China, was analysed by nucleotide sequencing or polymerase chain reaction-restriction fragment length polymorphism. HBV-C1/Cs (n = 112, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…All samples were subjected to heminested PCR to find the specific mutations in the enhancer II/core promoter and precore/core regions and to confirm the PCR-restriction fragment length polymorphism results of the genotypes/subgenotypes as previously reported (33). Amplified products were directly sequenced in both the forward and reverse directions using an ABI 3700 sequencer and commercial kit (Applied Biosystems, Foster City, CA).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were subjected to heminested PCR to find the specific mutations in the enhancer II/core promoter and precore/core regions and to confirm the PCR-restriction fragment length polymorphism results of the genotypes/subgenotypes as previously reported (33). Amplified products were directly sequenced in both the forward and reverse directions using an ABI 3700 sequencer and commercial kit (Applied Biosystems, Foster City, CA).…”
Section: Patientsmentioning
confidence: 99%
“…In northern China, more than 90% of patients were infected with subgenotype C2, while in southern China, the predominant subgenotype was C1 (33). In the present study, we aimed to investigate the clinical and virological differences of subgenotypes Ba, C1, and C2, as well as the possible significant factors in HCC development.…”
mentioning
confidence: 99%
“…The results of the sequences analysis of these two products were combined and, as a result, the base sequence of all HBV-DNA regions was identified ( Figure 1). DNASIS R gene analysis software (Hitachi Electronics Engineering Co., Ltd.) was applied to compare the base sequence obtained by us with the sequences of already registered genomes of four HBV strains, DQ478885, AP011098, AB367417 and AB246344 [9][10][11][12][13] , using National Center for Biotechnology Information Basic Local Alignment Search Tool. As a result, the sequence for the genotype was 2C and matched 98% of the sequences of each of these 4 control strains.…”
Section: Case Reportmentioning
confidence: 99%
“…R gene analysis software was applied to compare the base sequence with the sequences of already registered genomes of 4 hepatitis B virus strains: DQ478885, AP011098, AB367417 and AB246344 [10][11][12][13] , using Basic Local Alignment Search Tool. PCR amplification products were obtained at high rates, although the rates were lower for other regions [6] .…”
Section: Figure 1 Nucleotide and Amino Acid Sequences Of The Prex Andmentioning
confidence: 99%
“…Moreover, the potential number of chemokines produced by hepatocytes and HCC cells might be higher than that by other cells (monocytes, endothelial cells, and hepatic stellate cells) (31,35,36). It has been reported that the progression of CH-B and HCC with persistent HBV infection is different among HBV genotypes (37)(38)(39)(40)(41)(42). Therefore, the expression patterns of the chemokines produced from HBV-replicating HCC could differ among the HBV genotypes and affect the immunopathogenesis of HBV-related HCC.…”
mentioning
confidence: 99%